Black Turpentine Beetle, Dendroctonus terebrans (Olivier) (Insecta: Coleoptera: Curculionidae: Scolytinae) - Albert E. Mayfield; Jiri Hulcr; John L. Foltz (EDIS)
Black turpentine beetles bore into the inner bark of stressed or injured pines, where they breed and feed on phloem tissue. Adults are strongly attracted to volatile pine odors and readily breed in fresh stumps. In typical forests, infestations do not exhibit the rapid and devastating expansion characteristic of the closely related southern pine beetle, but in stands where stress conditions are frequent or persistent, black turpentine beetle can become a chronic pest and cause significant mortality over an extended period of time. Historically, black turpentine beetle has been a major pest of pines wounded or treated with herbicides in naval stores production. During the 1950s, black turpentine beetle damaged 37 million board feet of timber and contributed to the financial collapse of turpentine farms. This revised 5-page fact sheet was written by Albert E. Mayfield, John L. Foltz, and Jiri Hulcr, and published by the UF Department of Entomology and Nematology, June 2015. (Photo credit Adam Black and Jiri Hulcr, UF/IFAS)